Kelayakan Bahan Ajar Berbantuan Media Flipbook Pada Materi Ikatan Kimia SMA Fase F - Elath, Yumty Y.; Waworuntu, Freetje; Kumajas, Jenny (General Chemistry Journal, 2025)
This study aims to test the feasibility of Flipbook media -assisted chemical bonding materials for Fase F. High School. The research method used is descriptive. This research consists of three stages, namely manufacturing, validation, and repairing teaching materials assisted by flipbook media. Validation uses a research instrument in the form of an assessment questionnaire that includes format, content, language, practicality, and effectiveness, which consists of 14 criteria. Validation of Flipbook media assisted teaching materials is carried out by five validators consisting of lecturers in the FMIPA-K Chemistry Department of Manado State University. The results showed the average total validation (RTV) of 3.56. Based on Khabibah in Yamasari (2010), this teaching material is classified as valid.